Citric acid and EDTA on the growth, photosynthetic properties and heavy metal accumulation of Iris halophila Pall. cultivated in Pb mine tailings. (March 2018) - Han, Yulin; Zhang, Lili; Gu, Jiguang; Zhao, Jiuzhou; Fu, Jiajia
Abstract: The effect of citric acid (CA) and EDTA on the growth, root and leaf anatomical structure, photosynthetic properties and lead (Pb) accumulation in Iris halophila seedlings cultivated in Pb mine tailings for 30 days were studied. Results showed that the dry weights of above-ground parts and underground parts of I. halophila under the treatments of 2 mmol kg −1 CA increased significantly and the tolerant index (IT) value treated with 2 mmol kg −1 EDTA was 19% lower than the control. The contents of photosynthetic pigments increased and decreased significantly with 0.5 mmol kg −1 CA and 2.0 mmol kg −1 EDTA, respectively. The leaf anatomic structure was negatively impacted by 2.0 mmol kg −1 EDTA. Treatment of 2 mmol kg −1 CA enhanced Cd and Zn accumulation in the above-ground parts, and Pb, Cu, Cd and Zn accumulation in the underground parts. EDTA treatments promoted Pb and Cd accumulation in both parts of I. halophila . The results indicated that the addition of organic acids could promote Pb and Cd accumulation and I. halophila could serve as pioneer species to be used in remediation of Pb mine tailings to improve the harsh environment. Highlights: Iris halophilais a Pb tolerant species. The dry weights of I. halophila could be enhanced by the treatments of 2 mmol kg −1 citric acid (CA). The leaf anatomic structure was negatively impacted by 2.0 mmol kg −1 EDTA treatment. EDTA treatments promoted Pb and Cd accumulation in both above and under-ground parts of I. halophila. I. halophila could serve as pioneer species in remediation of Pb tailings.